Infiltrating T lymphocytes and tumor microenvironment within cholangiocarcinoma: immune heterogeneity, intercellular communication, immune checkpoints - Dai, Yunyan; Dong, Chenyang; Wang, Zhiming; Zhou, Yunpeng; Wang, Yi; Hao, Yi; Chen, Pinggui; Liang, Chaojie; Li, Gaopeng (Frontiers in Immunology, 2025)
Cholangiocarcinoma is the second most common primary liver cancer, and its global incidence has increased in recent years. Radical surgical resection and systemic chemotherapy have traditionally been the standard treatment options. However, the complexity of cholangiocarcinoma subtypes often presents a challenge for early diagnosis. Additionally, high recurrence rates following radical treatment and resistance to late-stage chemotherapy limit the benefits for patients. Immunotherapy has emerged as an effective strategy for treating various types of cancer, and has shown efficacy when combined with chemotherapy for cholangiocarcinoma. Current immunotherapies targeting cholangiocarcinoma have predominantly focused on T lymphocytes within the tumor microenvironment, and new immunotherapies have yielded unsatisfactory results in clinical trials. Therefore, it is essential to achieve a comprehensive understanding of the unique tumor microenvironment of cholangiocarcinoma and the pivotal role of T lymphocytes within it. In this review, we describe the heterogeneous immune landscape and intercellular communication in cholangiocarcinoma and summarize the specific distribution of T lymphocytes. Finally, we review potential immune checkpoints in cholangiocarcinoma.